Gestión del departamento de crédito y cobranzas de la Cooperativa 13 de Abril de Babahoyo - Choca Ordoñez, Jessenia Ruby (2019)
In the cooperative April 13, there have been shortcomings in the recovery of the past due portfolio to because they do not have a credit officer and collections therefore there is a need to make a study to analyze how the lack of these personnel in the cooperative influences since the inappropriate management of credit approval in a financial institution impacts its liquidity The objective is to conduct a study to analyze how the lack of these personnel influences the Babahoyo cooperative. For the investigation the methodology of descriptive research, interview and documentation was applied. It is concluded that the management and strategies that apply for the recovery of past due loans are not adequate, therefore it is affecting its liquidity